A influência das inteligências cultural e emocional no sucesso do projeto - Calçada Junior, Laurival Siqueira (2021)
In this analysis we studied the influence of emotional and cultural intelligences on the success of the projects, an empirical, quantitative study. Through a questionnaire with 231 qualified respondents, I applied the techniques of factor analysis and linear regression to identify whether there is an impact of the intelligences on the success of the projects. The results show that there is a positive and significant influence for the emotional intelligence factors in the success of the projects. As for cultural intelligence we find significant influence with the factor cognitive and behavioral cultural intelligence, and negative significance with the motivational cultural intelligence and cognitive goal. We realized that the feeling of belonging to the project is positively significant for the success of the project, opening an important research agenda. The data shows that customer satisfaction and the iron triangle (scope, cost, time and quality) are recognized in successful projects and that factors of cognitive and behavioral cultural intelligence are related to success, emotional intelligence, self-knowledge, self-control and focus are also related to the success of the project. I intend to contribute to the literature showing that the study of emotional and cultural intelligences relations are relevant to the academy and in practice to present to organizations and project managers the need to develop skills in these areas, in order to improve the performance of the project.